Distortions to Agricultural Incentives in Eastern Europe and Central Asia - Anderson, Kym (World Bank, Washington, DC, 2017)
In a recent survey of European economic growth since 1950, Crafts and Toniolo (2008) conclude that incentive structures are a crucial explanator of comparative growth rates of the economies of east and west Europe. Pre-empting that, a 2006 report on trade performance and policies in Eastern Europe and Central Asia included as one of its key recommendations the need to reduce the mean and variance of the tariff equivalents of trade barriers, and in particular to reduce unilaterally the policy regimes' anti-export bias, especially in countries exporting primary products (Broadman 2006). To progress such reform in Europe's transition economies efficiently and effectively, and to see how recent policies line up with those of the European Union (EU), requires better information on the extent of reform during the past two decades and of current policy influences on incentives within and between sectors. Immediately prior to their transition to market economies, policies in the region greatly distorted producer and consumer incentives, especially for agricultural products. Those distortions have been reduced substantially in several countries, but large variations remain across the region and distortions appear to be growing again in some countries. Now is thus an opportune time to examine how policies affecting agriculture are evolving in this region, including as part of the adjustment to EU accession for ten of the transition economies in the region.